1996
DOI: 10.1083/jcb.135.4.1027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pinin, a novel protein associated with the desmosome-intermediate filament complex.

Abstract: Abstract. We have identified a protein named pinin that is associated with the mature desmosomes of the epithelia (Ouyang, P., and S.P. Sugrue. 1992. J. Cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 59 publications
1
58
2
1
Order By: Relevance
“…Prior in vitro studies demonstrated that PNN overexpression results in the enhanced epithelial phenotype characterized by increased cell-cell adhesion and decreased motility (Ouyang and Sugrue, 1996;Shi et al, 2000bShi et al, , 2001). Down-regulation of PNN by shRNA causes cells to become less adherent and more migratory and leads to down-regulation of several key adhesion molecules, including desmoplakin, ZO-1, and E-cadherin, which is a hallmark of neoplastic transformation (Joo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Prior in vitro studies demonstrated that PNN overexpression results in the enhanced epithelial phenotype characterized by increased cell-cell adhesion and decreased motility (Ouyang and Sugrue, 1996;Shi et al, 2000bShi et al, , 2001). Down-regulation of PNN by shRNA causes cells to become less adherent and more migratory and leads to down-regulation of several key adhesion molecules, including desmoplakin, ZO-1, and E-cadherin, which is a hallmark of neoplastic transformation (Joo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…4). We also isolated pinin, a desmosome-associated protein (48). Although no functional connection between pinin and splicing has been demonstrated, pinin localizes to splicing speckles in both Xenopus spp.…”
Section: Cloning and Analysis Of Murine Prp4k And Its Homologuesmentioning
confidence: 99%
“…Yeast two-hybrid assay and co-immunoprecipitation experiments demonstrated that Pnn interacts with several splicing-related SR family proteins, including SRp75, SRm300, SRp130, SRcyclophilin and RNPS1 and binds preferentially to splicedmRNA (Li et al, 2003;Lin et al, 2004;Zimowska et al, 2003). Apart from its roles within the nucleus, Pnn has also been shown to be involved in other cellular functions including the enhancement of cell-cell adhesion (Ouyang and Sugrue, 1996) and corneal cell migration (Shi et al, 2000b). Abnormal expression of Pnn in tumor cells has also been reported (Shi et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Pinin (Pnn), a SR-related protein, was originally characterized as a desmosome-associated protein found at the cytoplasmic face of the desmosome plaque at the convergence of intermediate filaments (Ouyang and Sugrue, 1992;Ouyang and Sugrue, 1996). Subsequent studies have demonstrated that Pnn not only exists at epithelial cell-cell contact sites, but also localizes in the nuclear 'speckle' domain, a subnuclear region for assembly and storage of splicing factors (Brandner et al, 1997;Ouyang, 1999).…”
Section: Introductionmentioning
confidence: 99%